Outcome of premature babies with RDS using bubble CPAP - Arora, Vivek; Gediya, Sandip G; Jain, Rupali (International Journal of Contemporary Pediatrics, 2017)
Background: Respiratory distress syndrome (RDS) contributes significantly to mortality and morbidity. Continuous positive airway pressure (CPAP), when applied to premature infants with RDS, re-expands collapsed alveoli, splints the airway, reduces work of breathing and improves the respiration. Objectives: To ascertain the immediate outcome of preterm infants with RDS on Bubble CPAP and identify risk factors associated with its failure. Methods: This was a prospective analytical study and inborn preterm infants (gestation 28 to 34 weeks) admitted to the NICU with RDS were included in the study. All the spontaneously breathing infants were stared on bubble CPAP and different variables were recorded. Those in whom CPAP failed were given surfactant and mechanical ventilation. Results: 170 neonates were enrolled in the study. 52 (30.5%) babies failed CPAP. The predictors of failure were; partial or no response to Antenatal Steroids (ANS), white-out on the chest X-ray, Silverman Anderson scoring >6 or FiO2 > 0.4 after 15-20 minutes of CPAP, extreme prematurity. Other maternal and neonatal variables did not influence the need for ventilation. Rates of mortality and duration of oxygen requirement was significantly higher in babies who failed CPAP. No baby had chronic lung disease. Conclusions: Infants with no or partial exposure to antenatal steroids, white-out chest X-ray and those with higher FiO2 requirement after initial stabilization on CPAP are at high risk of CPAP failure (needing mechanical ventilation). Bubble CPAP is safe for preterm infants with RDS; it decreases need of surfactant and mechanical ventilation.